The Effect of Big Five Personality on Performance of Beringharjo Market Batik Traders With Coaching As A Mediation - Wahyuni, Purbudi; Kusumawati, Diana Anggraini; Damayanti, Rizky Wahyuning (AIBPM Publisher, 2023)
This study aims to identify and analyze the influence of Big Personality Five Personalities (Extraversion, Agreeableness, Conscientiousness, Emotional Stability, and Openness to Experience) on MSME Performance for Traders in the Beringharjo Market with coaching as a mediating variable. The number of respondents in the study was taken by purposive random sampling with a sample of 98 traders at the market in Yogyakarta who were able to exist selling during the Covid-19 pandemic. The analytical method uses quantitative methods with SEM-PLS analysis tools in this study. The results of the analysis of this study are extraversion, openness to experience, and agreeableness have a significant positive effect on MSME performance. Neuroticism personality has a significant negative effect directly and indirectly with coaching as a mediator on the MSME performance of traders at Beringharjo Market.